A Link between Oil Price and Stock Market Index: The Case of Three Countries - Katenova, Maya; Syzdykov, Zhanat (Asian Journal of Economics and Empirical Research, 2018)
This study empirically explores the causal relationship between the stock market development and oil price in Russia, UK and Kazakhstan. With this aim, the data between 2000 and 2017 was used. This data was obtained from Bloomberg. The data includes Index KASE, RTS Index, FTSE Index and oil price. In order to find out the dependence between oil price and indexes of United Kingdom, Russian Federation and Kazakhstan (FTSE 100 index, RTS index and index KASE respectively) it was necessary to collect the data first of all. For the analysis it was decided to choose, as variables, the prices and trade volumes of chosen instruments. As it was mentioned previously, I looked through the 17-year period starting from January 1st, 2000 lasting January 1st, 2018. Monthly data was retrieved from Bloomberg. The purpose of the empirical analysis is to determine what kind of relationship, if any, exists between oil price and such stock indices as KASE Index, RTS Index and FTSE Index. This study investigates the interaction between the oil price and three indices. Quite an interesting fact is that there are no any significant relationships between oil price and indexes studied. Among all indices studied, Index KASE is the most dependent on oil prices. The least dependent index is FTSE index. It is important to understand that every country has its own research environment and special features, which also could be researched independently. Taking into consideration the importance of oil export earnings to the growth profile of the Kazakhstani economy, higher oil export revenues would result in the growth of Index KASE. Majority of companies listed in Kazakhstani index are export oriented. Thus, the study can serve as a promising avenue for further research. For example, for Kazakhstan, some new research indicators can be added, such as weight of export and import.